The Alpha Magnetic Spectrometer (AMS) on the international space station: Part II — Results from the first seven years - M.Aguilar; L.Ali Cavasonza; G.Ambrosi; L.Arruda; N.Attig; F.Barao; L.Barrin; A.Bartoloni; S.Başeğmez-du Pree; aJ.Bates; R.Battiston; M.Behlmann; et al. (Elsevier B.V., 2025)
The Alpha Magnetic Spectrometer (AMS) is a precision particle physics detector on the International Space Station (ISS) conducting a unique, long-duration mission of fundamental physics research in space. The physics objectives include the precise studies of the origin of dark matter, antimatter, and cosmic rays as well as the exploration of new phenomena. Following a 16-year period of construction and testing, and a precursor flight on the Space Shuttle, AMS was installed on the ISS on May 19, 2011. In this report we present results based on 120 billion charged cosmic ray events up to multi-TeV energies. This includes the fluxes of positrons, electrons, antiprotons, protons, and nuclei. These results provide unexpected information, which cannot be explained by the current theoretical models. The accuracy and characteristics of the data, simultaneously from many different types of cosmic rays, provide unique input to the understanding of origins, acceleration, and propagation of cosmic rays.